Handbook of digital games - Angelides, Marios C.; Agius, Harry (Hoboken, NJ : IEEE Press-Wiley, 2013)
"The first book to draw the various traditional and emerging facets of gaming together into a single volume, Handbook of Digital Games explores all the necessary facets to design modern digital game, including MPEG-4, MPEG-7, MPEG-21, Virtual Reality, autonomous Artificial Intelligence, social media function, and multi-generational aspect of modern computer games. Featuring over twenty-five international experts from both academia and game industry, this valuable handbook covers all the basics and current trends of computer games for the engineers in the game industry"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Computer games; Video games; GAMES -- Board; Computer games; Video games; Electronic books